Renal allograft biopsies in Hospital Selayang: An overview - Noriah O; Shahawiah AW; Nik Hasimah NY; Noor Laili MM; Nur Syahrina Rahim (College of Pathologists, Academy of Medicine Malaysia, 2024)
Non-Indexed Publication